Audit Mini Komunikasi Quality Assurance (AKQUA) untuk Peningkatan Kinerja Karyawan PT Sinar Djaja Can - Agus Suprianto; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2017)
The purpose of this research is to know the influence of Quality Assurance (QA) communication to improve employee performance of production department at PT Sinar Djaja Can reviewed in mini audit communication that is from management, organization, communication, and feedback aspects. This research uses quantitative explanative method, with total population of 200 employees of production department. Samples taken as many as 67 employees. The sampling technique uses simple random sampling technique. While the data analysis technique through multiple linear regression formula. The results of this study show that employee performance is influenced by management, organization, communication, and feedback. This is reinforced by R Square of 90.9%. This can be interpreted if the QA communication is improved then the performance of employees will increase in terms of quality, quantity, and utilization of time, so as to minimize the decline in quality standards of production and customer complaints. The other aspects are influenced by other variables outside the study.